The impact of foreign direct investments on poverty reduction in the Western Balkans - Margerita Topalli; Meri Papavangjeli; Silvester Ivanaj; Blerta Ferra (Economics: The Open-Access, Open-Assessment Journal, 2021)
This article empirically examines the impact of foreign direct investment (FDI) inflows on poverty in six Western Balkan countries and also considers other country characteristics, such as the human development index (HDI), corruption, investment freedom, economic freedom, trade openness, and fertility. The work presents estimations based on a generalized method of moments (GMM) estimator for panel data models with fixed effects during the period from 2002 to 2021. Our results show that FDI has significantly contributed to poverty reduction in the Western Balkan countries. However, attention should be paid to where and how FDI takes place as these investments should be directed at the productive sectors of the economy, thus leading to a higher impact on poverty and inequality. The study also finds that policies and institutions that support a country's economic freedom and openness are imperative for poverty reduction. In addition, poverty reduction in the Western Balkan region can be achieved through measures that contribute to the improvement of HDI and strengthen institutions to combat corruption. Nevertheless, the empirical results of the paper are subject to a number of drawbacks, such as the limited number of observations and the considerable amount of missing data, some of which is probably questionable, a phenomenon that is quite common for developing countries.
Keywords: 330; foreign direct investment; multinational enterprises; poverty alleviation; sustainable development goals; Western Balkans